Rising Income Inequality : Technology, or Trade and Financial Globalization? - Papageorgiou, Chris (IMF Working Papers; Working Paper, 2008)
We examine the relationship between trade and financial globalization and the rise in inequality in most countries in recent decades. We find technological progress as having a greater impact than globalization on inequality. The limited overall impact of globalization reflects two offsetting tendencies: whereas trade globalization is associated with a reduction in inequality, financial globalization-and foreign direct investment in particular-is associated with an increase. A key finding is that both globalization and technological changes increase the returns on human capital, underscoring the importance of education and training in both developed and developing countries in addressing rising inequality.